Zinc Administration Affects Bronchial Mucosal NF-κB p105/p50, p-NF-κB p65, IL-8, and IL-1β of Zinc-deficient Rats - Reza Gunadi Ranuh; Andy Darma; Alpha Fardah Athiyyah; Ergia Latifolia; Retno Asih Setyoningrum; Boerhan Hidajat; Siti Nurul Hidayati; Anang Endaryanto; Ferry Sandra; Subijanto Marto Sudarmo (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Risk of acute respiratory infections in children less than 5 years of age is up to 95%. Zinc deficiency is one of the main risk factors. This study aimed to explore the effect of zinc on the bronchial mucosae inflammatory status expressed by nuclear factor (NF)-κB p105/p50, NF-κB p65, interleukin (IL)-8, and IL-1β.METHODS: Twenty-four Wistar rats were divided into 4 groups: normal zinc diet group without zinc supplementation (Z1), normal zinc diet group with zinc supplementation (Z2), zinc deficient diet group without zinc supplementation (Z3), and zinc deficient diet group with zinc supplementation (Z4). NF-κB p105/p50, p-NF-κB p65, IL-8, and IL-1β were measured by immunohistochemical staining.RESULTS: The inflammatory status of bronchial mucosae between Z1 and Z2 groups showed no difference (p=0.055). However, the inflammatory status of bronchial mucosae between Z3 and Z4 groups showed significant difference (p<0.01). Multivariate factorial design showed that zinc supplementation was beneficial when given to zinc deficient diet group with regard to decrease p-NF-κB p65, IL-8 and IL-1β levels (p<0.001) and increase dendritic cell (p=0.022).CONCLUSION: Zinc administration under conditions of zinc deficiency affects the inflammatory status, as shown by the decrease of p-NF-κB p65, IL-8 and IL-1β and the increase of NF-κB p105/p50.KEYWORDS: zinc, NF-κB, p105/p50, p65, IL-8, IL-1β, rat